2002
DOI: 10.1016/s1535-6108(02)00207-6
|View full text |Cite
|
Sign up to set email alerts
|

E2F4 loss suppresses tumorigenesis in Rb mutant mice

Abstract: The E2F transcription factors mediate the activation or repression of key cell cycle regulatory genes under the control of the retinoblastoma protein (pRB) tumor suppressor and its relatives, p107 and p130. Here we investigate how E2F4, the major "repressive" E2F, contributes to pRB's tumor-suppressive properties. Remarkably, E2F4 loss suppresses the development of both pituitary and thyroid tumors in Rb(+/-) mice. Importantly, E2F4 loss also suppresses the inappropriate gene expression and proliferation of pR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 44 publications
4
102
2
1
Order By: Relevance
“…It has been demonstrated that E2F transcription factors that normally bind pRb (i.e. E2F1, E2F2, E2F3) may bind p107 in Rb-deficient cells (Lee et al, 2002). Our results support this observation and further indicate that functional compensation in Rb-deficient keratinocytes by p107 crucially depends on the absolute levels of p107 protein.…”
Section: Discussionsupporting
confidence: 86%
“…It has been demonstrated that E2F transcription factors that normally bind pRb (i.e. E2F1, E2F2, E2F3) may bind p107 in Rb-deficient cells (Lee et al, 2002). Our results support this observation and further indicate that functional compensation in Rb-deficient keratinocytes by p107 crucially depends on the absolute levels of p107 protein.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, cooperation occurs between Rb loss and the inactivation of Cip1, Kip1, Arf or Trp53 as judged by shortened survival and increased ILP tumor severity (Williams et al, 1994a;Brugarolas et al, 1998;Park et al, 1999;Tsai et al, 2002), as does cooperation between Ink4c and Kip1 or Cip1 for increased ILP tumor severity and shortened survival (Franklin et al, 1998(Franklin et al, , 2000. In contrast, loss of E2f1 or E2f4 lengthened survival and decreased the penetrance of the ILP tumors (Yamasaki et al, 1998;Lee et al, 2002). More recently, loss of E2f3 has been shown to decrease the severity of the ILP tumors in Rb þ /À mice (Ziebold et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that inactivation of E2f1 inhibits neuroendocrine tumorigenesis in Rb þ /À mice by reducing the penetrance and severity of tumors, thereby extending the lifespan of Rb þ /À animals (Yamasaki et al, 1998). Curiously, inactivation of E2F4 also extends the lifespan of Rb þ /À animals by liberating more p107 and p130 to bind E2F family members normally bound by pRB (Lee et al, 2002). Loss of Cip1 (p21) enhances ILP tumorigenesis and shortens the lifespan of Rb þ /À animals (Brugarolas et al, 1998), as does loss of Kip1 (p27) (Park et al, 1999).…”
Section: Introductionmentioning
confidence: 96%
“…pRB can substitute for p107/p130 in the CERC, and may there by maintain normal regulation in p107/p130-deficient cells (Le Cam et al, 1999). In contrast, it is suggested that p107 and p130 might not substitute for pRB at the E2F-Sp1 element (except under unusual circumstances, Lee et al, 2002), leading to E2F derepression in pRB-deficient as well as in E2F1-3-deficient cells ( further showed that pRB is required for the recruitment of HDAC1 as well as for histone deacetylation within the cyclin E transcription initiation region (Morrison et al, 2002). Whereas pRB is expected to dissociate from the cyclin E promoter when phosphorylated in late G1, the E2F-Sp1 element was found to remain occupied and to be crucial to transcriptional activation (Botz et al, 1996;Le Cam et al, 1999), suggesting that activating E2Fs remain.…”
Section: Roles For Specific Pocket Proteins In the Regulation Of E2f-mentioning
confidence: 99%